Prognostic value of homocysteine and vitamin D in patients with ischemic heart disease before aorto-coronary bypass surgery - A. S. Nikonenko; K. O. Chmul; A. A. Nikonenko; V. V. Osaulenko; N. F. Efimenko (Ukrainian Journal of Cardiovascular Surgery, 2017)
Diseases of the cardiovascular system is one of the most acute medical and social problems of modern society. Ischemic heart disease (IHD) and cerebral stroke were and remain the leading cause of death and disability. It is established that in the development of IHD and its complications, at present, hyperhomocysteinemia and vitamin D deficiency are considered.The aim of the study was to study the effect of hyperhomocysteinemia and vitamin D deficiency on the course of coronary heart disease. The study analyzed the data of 65 patients who were divided into two groups, based on the prevalence of atherosclerosis. In all patients with ischemic heart disease, vitamin D deficiency and hyperhomocysteemia were more pronounced in case of multifocal atherosclerosis, which should be taken into account when prescribing medication after myocardial revascularization.